Comparing Supportive Properties of Poly Lactic-Co-Glycolic Acid (PLGA), PLGA/Collagen and Human Amniotic Membrane for Human Urothelial and Smooth Muscle Cells Engineering - Sharifiaghdas, Farzaneh; Naji, Mohammad; Sarhangnejad, Reza; Rajabi - Zeleti, Sareh; Mirzadeh, Hamid; Zandi, Mojgan; Saeed, Mahdi (Urology Journal, 2014)
<!–[if gte mso 9]> <![endif]–> Abstract Purpose: To compare human urothelial and smooth muscle cells attachment and proliferation using three different matrices; poly lactic-co-glycolic acid (PLGA), PLGA/collagen and human amniotic membrane (hAM). Materials and Methods: Human urothelial and smooth muscle cells were cultured and examined for expression of urothelium (pancytokeratin and uroplakin III) and smooth muscle cells [desmin and alpha smooth muscle actin (α-SMA)] markers. Cells were cultured on three scaffolds; PLGA, PLGA/collagen and hAM. Thereafter, they were analyzed for cell growth on days 1, 3, 7, 14 and 21 after seeding by 3-(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Scaffolds were fixed and processed for hematoxylin and eosin (H&E) staining and immunohistochemistry against their cell specific markers after 7 and 14 days of culture. Results: MTT assay results revealed that collagen has improved cell attachment features of PLGA and led to significant increase of MTT signal in PLGA/collagen compared to PLGA (P < .001) and hAM (P < .001). hAM was a weaker matrix for both cell types as demonstrated in MTT assay and scanning electron microscope (SEM) images. SEM micrographs showed normal phenotype and distribution on PLGA and PLGA/collagen. In the same line, cells formed a well-developed layer either on PLGA or PLGA/collagen, which maintained expression of their corresponding markers. Conclusion: Our findings demonstrated significant improvement of cell attachment and growth achieved by collagen coating (PLGA/collagen) compared to PLGA and hAM. hAM despite of its natural entity was a weaker matrix for bladder engineering purposes. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>